IDENTITAS HIBRID ORANG CINA INDONESIA KRISTEN: Ketegangan dan Negosiasi antara Kecinaan, Keindonesiaan dan Kekristenan - , Darwin Darmawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research try to unpack Chinese Indonesian Christian identity negotiation in post Soeharto. More specifically, this research try to unpack the agency of Christianity in Chinese Indonesian identity negotiation. I conducted ethnographic research on the Indonesian Christian Church (Gereja Kristen Indonesia, GKI) in Perniagaan Street, Jakarta. GKI Perniagaan was chosen because of its rather unique position in that it has historically combined both Chinese tradition, Christian faith in ways that are quite different from the mainstream Indonesian community and history of Indonesian community. Using the concept of hybridity, this research has found that their identitities are heteregeneous, dynamic and ambivalent. This research has also found that there are continual tension and negotiation between Chineseness, Indonesianess and Christianity. That tension and negotiation produce hybrid self identification, i.e. Chinese Indonesian Christian. Relate to their hybrid self identification, Dutch Calvinisme, a branch of Protestantism, functions as âthird spaceâ where their hybrid identification of Chinese Indonesian Christian is possible to take place. Beside that, in the Christian third space they can answer the existensial question of what it means to be Chinese Indonesian Christian in post Soeharto. These findings contribute to debates over multiculturalism, especially regarding the perspective of seeing identity as hybrid not as fixed and essentialised way of understanding. The hybrid perspective of seeing identity helps us to live together in diversity.